(Dis)ability and development in Haiti: beyond one-dimensional views. Issue 3 (3rd May 2016) - Baranyi, Stephen; Louis, Ilionor
Abstract: The 2010 earthquake was a tragedy for Haitians: in addition to the 250, 000 lives lost and 1, 000, 000 persons displaced, 200, 000 persons became disabled. Although post-earthquake reconstruction efforts are seen by some as a failure, others have argued that they could be a model for the inclusion of disabled persons. This paper explores the grey zone between those interpretations. Based on original document and interview research, it shows how international support for disabled persons was driven by the organisation of that community into a social movement with representation in the state. It concludes by examining pending challenges from a critical perspective.